Effects of In-Plane Loading on Vibration of Composite Plates - E. Carrera; P. Nali; S. Lecca; M. Soave (Shock and Vibration)
This paper deals with the dynamic analysis of pre-stressed laminated composite plates. Particular emphasis is devoted to the case of in-plane mono-axial, biaxial, shear and combined loadings. Both equivalent single layer and layer-wise plate kinematic description are addressed, according to the hierarchical approach proposed by the Carrera's unified formulation. The different kinematic approaches are compared in order to identify the appropriate modeling for laminated composite plates subjected to combined loadings. The principle of virtual displacement is applied in order to obtain governing equations and the corresponding problem is solved through the finite element method. When possible, assessments/comparisons with exact solutions are proposed. Moreover, the effects of different stacking sequences, boundary conditions, geometries and materials on plate natural frequencies are illustrated.